2016
DOI: 10.18632/oncotarget.13006
|View full text |Cite
|
Sign up to set email alerts
|

HMGCS2 enhances invasion and metastasis via direct interaction with PPARα to activate Src signaling in colorectal cancer and oral cancer

Abstract: Mitochondrial 3-hydroxy-3-methylglutaryl-CoA synthase (HMGCS2) is the rate-limiting enzyme of ketogenesis. Growing evidence indicates that HMGCS2 may be involved in cancer progression, but its exact role is largely unknown. In this study, we demonstrate that HMGCS2 mRNA expression is associated with poor clinical prognosis and outcomes in patients with colorectal cancer (CRC) and oral squamous cell carcinoma (OSCC). In vitro, ectopic expression of HMGCS2 enhanced cancer cell motility in a ketogenesis-independe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
52
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(54 citation statements)
references
References 30 publications
1
52
1
Order By: Relevance
“…Excluding gut epithelial cells and hepatocytes, HMGCS2 is nearly absent in almost all other mammalian cells, but the prospect of extrahepatic ketogenesis has been raised in tumor cells, astrocytes of the central nervous system, the kidney, pancreatic β cells, retinal pigment epithelium (RPE), and even in skeletal muscle (Adijanto et al, 2014; Avogaro et al, 1992; El Azzouny et al, 2016; Grabacka et al, 2016; Kang et al, 2015; Le Foll et al, 2014; Nonaka et al, 2016; Takagi et al, 2016a; Thevenet et al, 2016; Zhang et al, 2011). Ectopic HMGCS2 has been observed in tissues that lack net ketogenic capacity (Cook et al, 2016; Wentz et al, 2010), and HMGCS2 exhibits prospective ketogenesis-independent ‘moonlighting’ activities, including within the cell nucleus (Chen et al, 2016; Kostiuk et al, 2010; Meertens et al, 1998). …”
Section: Controversies In Extrahepatic Ketogenesismentioning
confidence: 99%
See 1 more Smart Citation
“…Excluding gut epithelial cells and hepatocytes, HMGCS2 is nearly absent in almost all other mammalian cells, but the prospect of extrahepatic ketogenesis has been raised in tumor cells, astrocytes of the central nervous system, the kidney, pancreatic β cells, retinal pigment epithelium (RPE), and even in skeletal muscle (Adijanto et al, 2014; Avogaro et al, 1992; El Azzouny et al, 2016; Grabacka et al, 2016; Kang et al, 2015; Le Foll et al, 2014; Nonaka et al, 2016; Takagi et al, 2016a; Thevenet et al, 2016; Zhang et al, 2011). Ectopic HMGCS2 has been observed in tissues that lack net ketogenic capacity (Cook et al, 2016; Wentz et al, 2010), and HMGCS2 exhibits prospective ketogenesis-independent ‘moonlighting’ activities, including within the cell nucleus (Chen et al, 2016; Kostiuk et al, 2010; Meertens et al, 1998). …”
Section: Controversies In Extrahepatic Ketogenesismentioning
confidence: 99%
“…Alternatively, tumor cell ketogenesis has also been proposed. Dynamic shifts in ketogenic gene expression are exhibited during cancerous transformation of colonic epithelium, a cell type that normally expresses HMGCS2, and a recent report suggested that HMGCS2 may be a prognostic marker of poor prognosis in colorectal and squamous cell carcinomas (Camarero et al, 2006; Chen et al, 2016). Whether this association requires or involves ketogenesis, or a moonlighting function of HMGCS2, remains to be determined.…”
Section: Ketone Bodies In Cancer Biologymentioning
confidence: 99%
“…The HLD-specific deletion enhancer, SFA1 , has seven human homologs, of which three ( ADH4, ADH1A , and ADH6 ) were UES in gCSI data ( Additional File 1, Figure S7) ‥ High expression of ADH1A or ADH6 was predictive of improved prognosis for pancreatic adenocarcinoma [185] and high expression of ADH1A or ADH4 had improved prognosis for non-small cell lung cancer [186]. The ERG13 homolog, GCS1 , has been suggested as a synthetic lethal target for BRAF V600E -positive human cancers [187], and HMGCS2 plays a role in invasion and metastasis in colorectal and oral cancer [188]. Thus, doxorubicin treatment may have anti-tumor efficacy specifically in glycolytic tumors with reduced expression of SFA1 and ERG13 homologs.…”
Section: Resultsmentioning
confidence: 99%
“…Some studies have shown that HMGCS2 may relate to the progression of cancer and play a key role in enhancing the phenotype of tumor migration, invasion, and metastasis through an independent metabolic mechanism in vitro. HMGCS2 can also increase the heterotopic expression of cancer cells to enhance the vitality of cancer cells (Chen et al, ). Intestinal fatty acid binding protein 2 ( FABP2 ) is an intracellular protein, a highly specific marker of intestinal necrosis, expressed in intestinal epithelial cells and combined with saturated and unsaturated long‐chain fatty acids to participate in the absorption and transport of dietary fatty acids (Alharbi et al, ; Kano, Takahashi, Inoue, Tanaka, & Okita, ; Khattab, Abo‐Elmatty, Ghattas, Mesbah, & Mehanna, ).…”
Section: Discussionmentioning
confidence: 99%